Community-Oriented Primary Care: New Relevance in a Changing World - Mullan, Fitzhugh (American Public Health Association, 2002)
Since its inception in rural, pre-apartheid South Africa, community-oriented primary care (COPC) has intrigued and informed public health and primary care leaders worldwide. COPC has influenced such programs as the US community health center movement, the general practice movement in the United Kingdom, and recent reforms in the public health system of South Africa. We provide a global overview of COPC, tracing its conceptual roots, reviewing its many manifestations, and exploring its future prospects as an organizational paradigm for the democratic organization of community health services. We examine the pitfalls and paradoxes of COPC and suggest its future utility. COPC has important values and methods to offer disparate but powerful movements in public health worldwide.